[tex]\frac{2cos^2{\sqrt{x+1}}-2cos^2{\sqrt{x}}}{2}=\frac{cos{2\sqrt{x+1}}-cos{2\sqrt{x}}}{2}=-sin\left ( \sqrt{x+1}+\sqrt{x} \right ).sin\left ( \sqrt{x+1}-\sqrt{x} \right )=-sin\left ( \frac{1}{\sqrt{x+1}-\sqrt{x}} \right ).sin\left ( \frac{1}{\sqrt{x+1}+\sqrt{x}} \right )[/tex]
=> [tex]\lim_{x \rightarrow +\infty}\left ( cos^2{\sqrt{x+1}}-cos^2{\sqrt{x}} \right )=\lim_{x \rightarrow +\infty}\left ( -sin\left ( \frac{1}{\sqrt{x+1}-\sqrt{x}} \right ).sin\left ( \frac{1}{\sqrt{x+1}+\sqrt{x}} \right ) \right )=-sin\left (\lim_{x \rightarrow +\infty}\frac{1}{\sqrt{x+1}-\sqrt{x}} \right ).sin\left (\lim_{x \rightarrow +\infty}\frac{1}{\sqrt{x+1}+\sqrt{x}} \right )=0[/tex]
vì: [tex]sin\left (\lim_{x \rightarrow +\infty}\frac{1}{\sqrt{x+1}+\sqrt{x}} \right )=sin(0)=0[/tex]